Alcohol Consumption and Current Situation of Drinking Risk Level Among University Students in Mandalay Region - Yadanar Aung; Yin Thet Nu Ou; Nanda Myo Aung Wan; Bo Bo Nyan; Aung Pyae Phyo; Le Le Win (GHMJ (Global Health Management Journal), 2019)
Background: In Myanmar, alcohol consumption among university students had been recognized as a major public health concern. A cross-sectional study was done to investigate drinking alcohol and risk level assessment using the Alcohol Use Disorder Identification Test (AUDIT) and examined the reasons of alcohol uses and types of beverage preference consumed. Methods: The two universities from three districts in Mandalay region were randomly selected, from which 976 students (stratified by academic year and sex) were contributed in self-administered questionnaire. Results: The mean age at first drinking alcohol among the participants was 16.36_0.15 years with range of 16 to 19 years. The drinking risk level assessment using the AUDIT test, nearly half of the participants 48.7% were abstainers and 86 (8.8%) were high risk drinkers while 28 (2.9%) had alcohol dependency. Among those, 57.8% had experiences of alcohol drinking and the favorite beverage of the university students who drink alcohol was beer. Binary logistic regression analysis indicated that gender, smoking habit and living situation for drinking were significant predictors of alcohol consumption among university students. The results found out that living separately with parents and smoking habits were important factors for drinking alcohol with statistically significant at 95% confidence level. Conclusion: It provided evidence-based findings for knowing the alcohol consumption risk level among university students to prevent social deprivation and health risk behaviors. Findings from this study indicate a need for law governing, strictly prohibits the sale of alcohol directly or indirectly to those under the age of eighteen years. The alcohol intervention program can be helpful in modifying behaviors change communication in health promotion of university students. Keywords: Alcohol consumption, AUDIT test, drinking risk level, university students and binary logistic regression Received: 12 April 2019 Reviewed: 18 June 2019 Revised: 25 June 2019 Accepted: 8 July 2019 DOI: 10.35898/ghmj-33582